A look into the scientific situation of two essential specialities of contemporary nursing: anthropology of care and trans-cultural nursing - José Siles González; Luis Cibanal Juan; María Flores Vizcaya Moreno; Eva María Gabaldón Bravo; Juan Mario Domínguez Santamaría; María del Carmen Solano Ruiz; Encarnación García Hernández (Universidad de Alicante, 2012)
The general aim of this study is to explain the need for adopting transcultural methods and approaches within Iberian Nursing. To achieve this objective, it has been necessary to prove the anthropological nature of care and to identify the connection between the ideological frame of science and transcultural nursing. Materials and method: The heuristic method was used to search and select convenient sources and materials for the study (nursing models with an anthropological and/or transcultural approach). These materials have been dealt with from the sociocritic and hermeneutic paradigm perspective, thus enabling us to explain the ideological factor within the scientific context. Regarding results, the following models -which share the socioanthropological characteristics - have been identified, described and explained: Madelaine Leininger's rising sun model; Larry Purnel's cultural competence model; Rachel Spector's cultural heritage and health traditions model. Conclusions: for an adequate development of nursing science in a multicultural society, it is necessary to implement models that adopt anthropological approaches and consider the cultural and ideological factor as the object of study. In current nursing there are models that comply with those characteristics (rising sun, cultural competence, heritage and health traditions).